Moral Inversion and Apocalyptic Violence in Yeats’s “The Second Coming” - Bhattarai, Rajendra (International Research Journal of MMC, 2026)
This study aims to identify and analyze moral inversion and apocalyptic violence in W.B. Yeats’s “The Second Coming.” A qualitative documentary research design was employed to accomplish this study. Major poetic excerpts which reflected the moral inversion and apocalyptic violence in the poem were the sources of primary data, whereas relevant books and peer-reviewed journal articles were utilized as the sources of qualitative secondary data. Thematic analysis was applied to interpret the primary data. The findings indicate that Yeats’s “The Second Coming” functions as a powerful metaphor for moral inversion and apocalyptic violence. It reflects the persistent erosion of ethical and democratic values. The poem reveals that the “lack of conviction” among the virtuous is not merely a historical condition but a recurring phenomenon that continues to shape periods of social and political crisis. The analysis reveals that Yeats portrays a world where traditional virtues are systematically replaced by predatory chaos. This article highlights the enduring relevance of Yeatsian prophecy in understanding contemporary global crises.